MSCI Downgrade to Frontier Market: Lessons for Indonesia from Three Countries - Muhammad Ananda Fakhri; Farianita Lestari; Berry Dhiyashavana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study investigates the impact of MSCI reclassification from Emerging Market (EM) to Frontier Market (FM) on stock market return and capital flow dynamics, using a comparative approach across three historical cases: Jordan (November 2008), Argentina (May 2009), and Morocco (November 2013). The research employs two complementary methods: (1) an event study using daily stock index data from Investing.com, measuring cumulative abnormal returns (CAR) via the Market Model with MSCI World Index as benchmark, tested using the Brown-Warner BMP test; and (2) a before-after analysis using annual Balance of Payments data from the World Bank (indicator BN.KLT.PTXL.CD), tested using the Wilcoxon Signed-Rank Test. All statistical analyses were performed using RStudio 2024.09.2+398. Results show that Jordan experienced the most severe impact with CAR reaching -54.43% (p<0.01) at ED [-20,+60] and -71.35% (p<0.01) at ED [-60,+120], confirming the Price Pressure Hypothesis. Morocco exhibited limited short-term price impact due to an FM premium effect, but recorded a net foreign flow decline of USD -1.554 billion post-downgrade. Argentina showed anomalous positive CAR attributed to Global Financial Crisis recovery effects coinciding with the downgrade period. These findings serve as empirical benchmarks for Indonesia, which faces a MSCI rebalancing freeze since January 2026 and potential downgrade risk ahead of the May 2026 review.